Sintesis de peliculas delgadas de AuNx por medio del sistema de deposicion fisica en fase vapor asistida por plasma(PAPVD) (2011)
New family of Transition Metallic Nitrides (NMT) has been obtained in the last decade. The 4d and 5d series of late transition metals (Ru, Rh, Pd, Ag, Os, Ir, Pt, and Au, , also known as noble metal) are generally considered not to form nitrides, however, since it was obtained the Ag_x N y el Au_x N, different investigation group began to synthesize and model some of them. Siller is the first in report about of synthesizing AuN in the 2002, it report as about binding energies, conductivity, possible structures, catalyzing, among others, it has been until now the research in the which she has advanced. In this work AuN thin films on 304 stainless steel was obtained for a Arc Pulsed - Plasma Assited Phase Vapor Deposition (PAPVD), and the results were compared with the Siller reports. The Nitrogen hybridization state in 398.1 eV and 398.3 eV are reported as new N1s hybridization state to gold nitride. Au4f spectral lines were deconvoluted and 84.3 eV y 84.7 eV hybridization state were found, the which it could be the Au hybridization state with the N to phase AuN. Changes in the Bragg Diffraction Lines were found, which through Rocking Curve were corroborated as interstitial nitrogen into Au lattice. In the 30% al 60% range, the nitrogen atoms prefer the octahedral sites of the Au lattice for found a phase restructuring as is known for NMT.